Ethical excellence philosophers, psychologists, and real-life exemplars show us how to achieve it - Geibel, Heidi M. (Washington, D.C. : The Catholic University of America Press, 2021)
"Combines insights from philosophy, psychology, and the biographies of ordinary people to identify principles to guide our ethical development and provide concrete models for an ethical life"--
Intro -- Contents -- Acknowledgments -- Introduction -- Part 1: Foundations of Ethical Excellence -- 1. Theoretical Foundations: Ethical Excellence and the Good Life -- 2. Practical Foundations: Recognizing Your Potential -- 3. Personal Foundations: Willpower -- Part 2: Knowing Yourself: The Good, the Not-So-Good, and the Potentially Good -- 4. Examining Your Life -- 5. Refusing to Rationalize -- 6. Honesty: The Courage to Tell the Truth -- Part 3: Fixing Your Flaws: Broadening Your View and Taming Your Inner Beast -- 7. Broadening Your View -- 8. Temperance: Taming Your Inner Beast -- 9. Perseverance: The Strength to Keep Going -- Part 4: Good Thing It's Not All about You: Understanding, Humility, and Learning by Example -- 10. Understanding Others -- 11. Identifying Role Models: Positive and Negative -- 12. Humility: Living with Your Limits -- Part 5: Giving People What They Deserve: What You Owe Your Parents, Your Benefactors, and People in General -- 13. Justice: Treating People Rightly -- 14. Piety: Revering Your Roots -- 15. Gratitude: Acknowledging Goodness -- Part 6: Extending Goodness: Next Door, across the World, and Everywhere in Between -- 16. Friendship: Keeping Good Company -- 17. Befriending the World -- 18. Benevolence and Generosity: The Most Lovable Virtues -- Part 7: Pursuing Wisdom-and What to Do until You Find It -- 19. Tying It All Together: Practical Wisdom and Ethical Virtue -- 20. When All Else Fails... -- Notes -- Bibliography -- Index.
JSTOR
Keywords: Excellence; Conduct of life; Excellence; Morale pratique; ethics (philosophical concept); Conduct of life; Excellence